The Orbiniidae (Annelida: Polychaeta) of Pacific Costa Rica - Dean, Harlan K.; Blake, James A. (Zootaxa, 2015)
Seven species of Orbiniidae are described from the Pacific coast of Costa Rica including two new species. Leodamas hamatus n. sp., a commonly occurring species on the coast of Pacific Costa Rica, is described from 11‒18 m in the Gulf of Nicoya and Bahia Culebra. This species is unusual in that the neuropodial uncini differ morphologically from anterior to posterior in the thorax. Scoloplos cryptospinigerus n. sp. is described from 18–22 m in the Gulf of Nicoya and has only a few short, toothed spines amidst numerous capillary setae in most of the thoracic neuropodia. This arrangement of thoracic neurosetae is unusual and has been seen only in one other described species of Scoloplos from Australia.